2022
DOI: 10.1021/acs.macromol.1c02387
|View full text |Cite
|
Sign up to set email alerts
|

Universal Scaling for the Exit Dynamics of Block Copolymers from Micelles at Short and Long Time Scales

Abstract: The correlation function for the exit of poloxamer copolymers from equilibrated micelles is found to show up to four regimes depending on the chain flexibility: an initial fast reorganization, a logarithmic intermediate regime, followed by an exponential intermediate regime, and a final exponential decay. The logarithmic intermediate regime has been observed experimentally and attributed to the polydispersity of the polymer samples. However, we present dynamic single-chain mean-field theory simulations with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition to DPD simulations, Mackie and co-workers have used a dynamical single-chain in mean-field (SCMF) simulations to model the dynamics of chain exchange in an array of micelles formed by triblock copolymers, again mimicking the TR-SANS experiment. A remarkable outcome of their calculations is the presence of a logarithmic decay despite their simulations using a monodisperse polymer . They argue that the logarithmic behavior emerges from a degeneracy in the states available to the solvophobic midblock in the micelle core that is destroyed when that block escapes from the micelle core.…”
Section: Chain Exchange In Solutionmentioning
confidence: 99%
“…In addition to DPD simulations, Mackie and co-workers have used a dynamical single-chain in mean-field (SCMF) simulations to model the dynamics of chain exchange in an array of micelles formed by triblock copolymers, again mimicking the TR-SANS experiment. A remarkable outcome of their calculations is the presence of a logarithmic decay despite their simulations using a monodisperse polymer . They argue that the logarithmic behavior emerges from a degeneracy in the states available to the solvophobic midblock in the micelle core that is destroyed when that block escapes from the micelle core.…”
Section: Chain Exchange In Solutionmentioning
confidence: 99%
“…Figure a shows that the normalized FRET efficiency E ( t )/ E (∞) without the addition of PS- b -PMAA increases continuously but not logarithmically. Previous works have observed that chain exchange kinetics of diblock copolymers follow a logarithmic relaxation pattern using time-resolved small-angle neutron scattering (TR-SANS), presumably due to the hypersensitive dependence of single-chain exchange rate on the core block length. ,, However, recent work by Mackie et al has suggested that logarithmic relaxation may also be observed for block copolymers with flexible monodisperse core chains using a dynamic single-chain mean-field theory simulation method, arising from a degeneracy of energy states of the monodisperse block in the micelle core. , In contrast, for the rigid core chain, the logarithmic relaxation is absent. Therefore, the lack of logarithmic relaxation in our study could be attributed to the rigidity of the PS block despite its relatively low polydispersity index (PDI) of 1.10.…”
Section: Resultsmentioning
confidence: 99%
“…5,9,15 However, recent work by Mackie et al has suggested that logarithmic relaxation may also be observed for block copolymers with flexible monodisperse core chains using a dynamic single-chain mean-field theory simulation method, arising from a degeneracy of energy states of the monodisperse block in the micelle core. 33,34 In contrast, for the rigid core chain, the logarithmic relaxation is absent. Therefore, the lack of logarithmic relaxation in our study could be attributed to the rigidity of the PS block despite its relatively low polydispersity index (PDI) of 1.10.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar soft gels or viscous complex fluids, loosely defined by G ′ > G ″ and 10 < G ′ < 1000 Pa, have been reported in other solutions of percolating BAB micelle clusters, ,, solutions of P407 blended with other poloxamers or RPs, ,, and over narrow temperature windows in commercial P407 solutions. , This soft gel exhibits significant viscoelastic aging with the dynamic moduli increasing over time when held at a constant temperature. Such aging is similar to that observed in colloidal glasses and attractive gels and suggests that the material is initially out-of-equilibrium but evolves over time through the breaking and reforming of attractive interparticle bonds, here involving PEO block bridging. For RP407 in water, individual polymer bridges are expected to be able to break and reform quickly, as the process of chain exchange is very rapid for poloxamers in water (<10 ms); however, achieving an equilibrium bridge fraction will require orders of magnitude more time than the single-chain exchange mechanism. , Furthermore, similar to the behavior of colloidal gels, the increasing viscosity of the medium likely slows diffusion of micelles.…”
Section: Discussionmentioning
confidence: 99%